Intersection of parabolic subgroups in Euclidean braid groups: a short proof - Cumplido, María; Gavazzi, Federica; Paris, Luis (Comptes Rendus. Mathématique)
We give a short proof for the fact, already proven by Thomas Haettel, that the arbitrary intersection of parabolic subgroups in Euclidean Braid groups $A[\tilde{A}_n]$ is again a parabolic subgroup. To that end, we use that the spherical-type Artin group $A[B_{n+1}]$ is isomorphic to $A[\tilde{A}_n]\rtimes \mathbb{Z}$ .